Site-Selective Bioconjugation via Interception of Free-Radical-Induced Dechalcogenation - Griffiths, Rhys (2021)
Peptides and proteins play numerous vital roles within cellular biochemistry, as a result they are central to our understanding of the molecular pathways essential to life and the development and progression of disease. The native biological influence of this class of biomolecule has led to the application of polypeptides as effective therapeutics, interest in which has steadily grown over the last four decades. This class of ‘biologic’ drug is now at the forefront of modern medicine. In order to exploit the biological properties of peptides and proteins to develop tools to investigate fundamental science and as therapeutic/diagnostic agents, synthetic methods that enable the site-selective installation of biologically relevant groups are required. There are a wide range of established techniques available which selectively target the canonical amino acids. The limitations of these methods include efficiency, operational simplicity, chemoselectivity, versatility and conjugate stability. There have been many recent advances that attempt to address these issues, but novel methods are still in high demand.